Correcting for focal spot drift in edge illumination X-ray phase contrast imaging - Nicholas Francken; Jonathan Sanctorum; Ben Huyge; Jan Sijbers; Jan De Beenhouwer (e-Journal of Nondestructive Testing)
Edge illumination is an X-ray phase contrast imaging technique that introduces two absorbing masks with slit-shaped apertures in the imaging setup. During an edge illumination acquisition, a pixel-wise intensity profile is measured by acquiring projections at several different mask aperture alignments. The difference in profile peak position between acquisitions with and without a sample yields the refraction contrast. However, the peak position itself depends on the source focal spot position. In many lab X-ray sources, the position of the focal spot can drift over time, causing a corresponding drift of the measured intensity profile peak. As edge illumination computed tomography scans typically have long acquisition times, they are particularly sensitive to errors caused by focal spot drift. In this work, the effect of focal spot drift on the edge illumination refraction contrast is measured. Post-processing correction methods to compensate for the intensity profile shift based on repeating projection angles and polynomial fitting are proposed and their effectiveness is demonstrated.